ICAM1+ gingival fibroblasts modulate periodontal inflammation to mitigate bone loss - Kim, William S.; Prasongyuenyong, Kawintip; Ko, Annette; Debnath, Rahul; Chen, Zhaoxu; Zhou, Jonathan X.; Shaaf, Emon; Ko, Kang I. (Frontiers in Immunology, 2024)
Tissue-resident fibroblasts are heterogeneous and provide an endogenous source of cytokines that regulate immunologic events in many osteolytic diseases. Identifying distinct inflammatory fibroblast subsets and conducting mechanistic in vivo studies are critical for understanding disease pathogenesis and precision therapeutics, which is poorly explored in periodontitis. Here, we surveyed published single-cell datasets for fibroblast-specific analysis and show that Intercellular Adhesion Molecule-1 (ICAM1) expression selectively defines a fibroblast subset that exhibits an inflammatory transcriptional profile associated with nuclear factor-κB (NF-κB) pathway. ICAM1+ fibroblasts expand in both human periodontitis and murine ligature-induced periodontitis model, which have upregulated expression of CCL2 and CXCL1 compared to other fibroblast populations. Using a mouse model to selectively target gingival stromal cells, we further show that disruption of an inflammatory pathway by inhibiting transcriptional activity of NF-κB in these cells accelerated periodontal bone loss. Mechanistically, this was linked to a reduction of CCL2 expression by the ICAM1+ fibroblasts, leading to impaired macrophage recruitment and efferocytosis that was associated with persistent neutrophilic inflammation. These results may have a significant therapeutic implication as ICAM1+ gingival fibroblasts exert a protective response by regulating innate immune responses that are needed for the controlled inflammatory events in early stages of periodontitis.